2019
DOI: 10.1080/14786419.2019.1644505
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anti-enteroviral activity of stilbenoids isolated from the leaves of Macaranga barteri

Abstract: The anti-enteroviral activity of three stilbenoids isolated from the leaves of Macaranga barteri was investigated using the cytopathic reduction assay. The stilbenes were inactive against echovirus E13 but showed activity against echoviruses E7 and E19. In particular, vedelianin (2), schweinfurthin G (3) and mappain (1) elicited antiviral activity on E19 with IC 50 values of 0.0036 nM, 0.018 nM and 0.24 µM, respectively. Vedelianin (2) showed the best selectivity profile amongst the isolated compounds with sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The pure compounds were tested against echovirus 7, 13 and 19 serotypes and were inactive against echovirus E13, while a good activity was reported on E19. In particular, vadelianin exhibited an IC 50 value of 0.0036 nM and the best selectivity profile with SI value of 216.7 [95].…”
Section: Compoundmentioning
confidence: 97%
See 1 more Smart Citation
“…The pure compounds were tested against echovirus 7, 13 and 19 serotypes and were inactive against echovirus E13, while a good activity was reported on E19. In particular, vadelianin exhibited an IC 50 value of 0.0036 nM and the best selectivity profile with SI value of 216.7 [95].…”
Section: Compoundmentioning
confidence: 97%
“…Conversely, cis-resveratrol exhibited significant Segun et al reported the anti-enteroviral activity of three stilbenoids (mappain, vadelianin and schweinfurthin G; Fig. 17) isolated from the leaves of Macaranga barteri (Euphorbiaceae) [95]. The pure compounds were tested against echovirus 7, 13 and 19 serotypes and were inactive against echovirus E13, while a good activity was reported on E19.…”
Section: Compoundmentioning
confidence: 99%
“…As an example, the strong in vitro activity of extracts of Macaranga barteri against E7 and E19 echoviruses suggests that it can be an effective therapeutic agent for enteroviral infections such as encephalitis (Ogbole et al, 2018). However, among all the components, three stilbenoids (especially vedelianin) isolated from M. barteri extracts are largely responsible for the anti-viral activity against echoviruses (Segun et al, 2019). Similarly, other stilbenes such as Resveratrol and trans-arachidin isolated from grapes and the hairy root culture of peanut are capable of reducing the replication rate of the African swine fever virus (ASFV) and RVs, respectively (Abba et al, 2015;Ball et al, 2015).…”
Section: Medicinal Plants and Their Extracts As An Anti-viral Agentmentioning
confidence: 99%
“…Most of the plants that found application in ethnomedicine have been documented based on their promising activities against multiple disease-causing microorganisms [ 7 , 8 ]. Research efforts are expediting for better functional understanding of medicinal plants, and this has provided a model for about 25–50% of the marketed drugs [ 9 ]. Antimicrobial activities of useful plants vary; the majority act in synergy [ 10 ], reducing the side effect of synthetic drugs [ 11 ], while others act as quorum quenchers [ 12 ].…”
Section: Introductionmentioning
confidence: 99%